Strategy Dynamic in Digital Transformation in Electric Utilities: Exploring the Role of System Dynamics - Banerji, Himadri (Digital Repository of Theses, 2025)
This research investigates how Smart Grids function as catalysts for digital transformation in electric utilities by applying Forrester's system dynamics modelling to analyse longitudinal data. The study examines feedback loops and policy scenarios and uncovers strategic opportunities and organizational challenges in pursuing carbon neutrality by 2050. Given that approximately 80% of digital transformation initiatives fail, this exploratory and action research aims to develop a comprehensive strategy dynamics framework to guide electric utilities through successful digital transformation. The methodological approach integrates theoretical frameworks from Pankaj Ghemawat's Strategy Dynamics and Gregory Vial's Digital Transformation Framework, enhanced by the researcher's 40+ years of executive leadership experience in major Indian electric utilities and as an advisor to a global consulting firm. The research methodology begins with Bibliometric Search Optimization that systematically demonstrates Smart Grids as key enablers of digital transformation, followed by an extensive empirical opinion survey yielding over 4,000 responses from academics, utility executives, policymakers, and senior consultants. Statistical analysis of this data informs the development of system dynamic archetypes and the final system dynamics model by formulating and testing five key hypotheses. This study addresses a significant gap in the literature, as no longitudinal System Dynamics study on strategy dynamics in electric utilities has been undertaken since Ford (1970) and Forrester (1980). By modeling the interdependencies between factors including energy demand, supply, pricing, consumer behavior, and regulatory policies, the research provides timely insights for utilities navigating the complexities of digital transformation. The resulting framework enables policymakers and industry stakeholders to simulate the behavior of complex smart grid ecosystems over time, identify leverage points for intervention, and inform strategic decision-making in the post-2020 landscape, particularly in sustainable energy transitions and accelerated business model innovations in retail electricity distribution.